Modified antituberculosis regimen due to hepatotoxicity caused by Pyrazinamide: Case report - Farfán-Chávez, Luis Gabriel (2023)
Introduction: Tuberculosis is one of the 10 leading causes of death worldwide. In 2020, it caused 1.5 million deaths. It is estimated that it reached 10.0 million new cases during the same year. Case of report: 93-year-old male, history of pulmonary TB 15 years ago and current TB contact. He presented dyspnea and pleuritic pain for 4 months. Thoracocentesis concludes exudate, pleural biopsy compatible with non-caseating granulomatous pleurisy. Receive antituberculosis regimen, developing hepatic RAFA. Pharmacological challenge is performed to design a new treatment scheme. Patient manages to recover. It is concluded that the management of tuberculosis should be individualized.